2017 IFIP/IEEE Symposium on Integrated Network and Service Management (IM) 2017
DOI: 10.23919/inm.2017.7987274
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a flexible Advance bandwidth Reservation Algorithm for media production networks

Abstract: Abstract-In media production companies, exchanging large media files is daily business. Due to the predictable nature of network transfers in the media production industry, timeslotbased advance bandwidth reservation results in higher bandwidth utilization and improved network performance. Timeslot-based advance reservation can be based on flexible or fixed timeslot sizes. As the flexible approach is highly beneficial under bursty and limited network traffic conditions, this paper focuses on that approach. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Most of them opt for the flexibility provided by dynamic time slots even if managing such structures is more complex. In [22], Barshan et al propose a mechanism for improving the admittance ratio of video transfers in media production networks, which are a specific use case characterized by an interdependence among different video transfers.…”
Section: E Summary Of Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them opt for the flexibility provided by dynamic time slots even if managing such structures is more complex. In [22], Barshan et al propose a mechanism for improving the admittance ratio of video transfers in media production networks, which are a specific use case characterized by an interdependence among different video transfers.…”
Section: E Summary Of Literature Review and Discussionmentioning
confidence: 99%
“…In [22], Barshan et al present a bandwidth reservation model specifically tailored to the characteristics of media production networks. The proposed solution is based on time slots of variable size, and a timeslot is a time interval in which reservations remain invariant.…”
Section: B Timing Constraintsmentioning
confidence: 99%
“…To cope with the high time complexity of reservation-based approaches, the timeslot-based approach has been proposed as an efficient way [2]. According to the way the time domain is processed, the existing timeslotbased approaches can be classified into the static timeslotbased approach [2], dynamic timeslot-based approach [2] and flexible timeslot-based approach [3]- [5]. The authors in [3] theoretically analyzed the advantages and drawbacks of the static and flexible timeslot-based approach and concluded that the static timeslot-based approach is less effective in terms of resource utilization than the flexible timeslot-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we further analyze the performance of the static, dynamic and flexible timeslot-based approaches in terms of resource utilization and computational complexity. Though the flexible timeslot-based approach is highly beneficial when dealing with bursty traffic in a low-demand network with long-term downtimes, it is ineffective in a highdemand network [3], [5]. A resilient AR approach based on flexible timeslots, in combination with a runtime adaptation approach, has been introduced to provide flexible, reliable and adaptive advance reservation to an AR system [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation